Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2002)
Table of Content The Logical Work of Xavier Veilhan by Véronique d’Auzac de Lamartinie Olafur Eliasson Beyond the Ambient by Ina Blom Gartensozialismus by Jessica Morgan Tom Friedman Same and Different by Dan Cameron Mapping Your World by Midori Matsui Serious Playboys by John Waters & Tom Friedman Rodney Graham A Tale of a Hat by Lynne Cooke And I’m Wondering Who Could Be Writing This Song by Mathew Hale Amy Sillman, Insert You’re in Trouble if You’re Eating by A.M. Homes & Chris Verene Annika Larsson – Dominance and Submission by Håkan Nilsson Parkett Inquiry: Learning from documenta
﻿On immersing oneself in the working practice of the collaboration artists in this issue, one soon surrenders to the feeling of observing strange, eccentric scientists. Olafur Eliasson creates sophisticated but elemental models to examine the conditioning of perception, above all the act of seeing itself; Rodney Graham devotes himself “body and soul” to states of consciousness, altering them artificially if need be; and Tom Friedman is as meticulous as a watchmaker in his concentration on the non-technical, non-mechanical and daily reality of the “blind spot.” (editorial by publisher)
boek
Keywords: Eliasson, Olafur; Graham, Rodney; Friedman, Tom